Problems of Ukrainian expressive discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The syntactical formations of expressive discourse are analyzed.  Their structural-syntactical features and functionality are examined. Attention is drawn to the importance of expressive means in the formation of information field, which find expression new forms of communication.
Keywords: expressive discourse; binary segmentation; segmentation; parcelling; the chain of nominative sentences; infinitive structures